Synthesis of Dihydroindoloisoquinolines through Copper‐Catalyzed Cross‐Dehydrogenative Coupling of Tetrahydroisoquinolines and Nitroalkanes. Issue 71 (26th November 2018) - Martín‐García, Iris; Alonso, Francisco
Abstract: Lately, the cross‐dehydrogenative coupling of tetrahydroisoquinolines and nitroalkanes has become a widely studied reaction in organic chemistry; the corresponding β‐nitroamines are generally formed irrespective of the catalysis and activation mode utilized. A quite distinct behavior was observed when the reaction was catalyzed by copper nanoparticles supported on titania, leading to the formation of 5, 6‐dihydroindolo[2, 1‐ a ]isoquinolines with high selectivity and good yields. A meticulous reaction mechanism is proposed, based on experimentation, and discussed along with a key chemical modification of these compounds. Apparently, the catalyst effectiveness resides in its nanostructured character, outperforming the activity of the commercial copper catalysts. Abstract : CuNPs make the difference ! A unique reaction of tetrahydroisoquinolines and nitroalkanes under the catalysis of supported copper nanoparticles is described in which dihydroindoloisoquinolines are produced instead of the corresponding and extensively reported β‐nitroamines. Notable features: simple and cheap catalytic system, aerobic and solvent‐free conditions, only slight excess of the nitroalkane, absence of additives (ligands, oxidants, etc.) and better catalytic activity than commercial catalysts.